Peran Pustakawan Dalam Manajemen Konflik Informasi di Perpustakaan - Fadilah, Cindy; Masruri, Anis (Universitas Negeri Padang, 2023)
Conflict is not a new phenomenon in the library environment, but librarians must be able to deal with it. Emotional intelligence is needed to create existing conflict management. Emotional intelligence is a skill related to emotions such as the ability to control individual and other people's anger so that managing anger is to examine thoughts and actions. Emotional management skills can help individuals understand and manage emotions and use information to influence thinking and behavior when interacting with others in certain organizations. Librarians must be able to deal with moods, emotions and feelings so that librarians don't get emotional easily and don't even affect their performance. It also helps build empathy because when a librarian understands her mood and other people's feelings. Thus introducing a person to work better with others and preventing conflicts.